Asthma in Adolescents: A Randomized, Controlled Trial of an Asthma Program for Adolescents and Young Adults with Severe Asthma - Robert L Cowie; Margot F Underwood; Cinde B Little; Ian Mitchell; Sheldon Spier; Gordon T Ford (Canadian Respiratory Journal)
BACKGROUND: Asthma is common and is often poorly controlled in adolescent subjects.